Pembelajaran Berdiferensiasi Sebagai Pendekatan Tranformasional Dalam Pendidikan Agama Islam Kontemporer - sihono sihono (JURNAL PENELITIAN DAN EVALUASI PENDIDIKAN, 2025)
This study aims to explore the concept and implementation of differentiated instruction in contemporary Islamic religious education as a transformational approach. Using a qualitative approach based on library research, this study examines recent literature to identify benefits, challenges, and relevant implementation strategies. The findings indicate that differentiated instruction enhances student engagement by tailoring teaching methods to individual needs, interests, and learning styles. This approach also fosters the internalization of Islamic values through personalized, contextual, and relevant learning experiences. However, its implementation faces challenges such as limited time, resources, and adequate teacher training. As a transformational approach, differentiated instruction requires teachers to adapt to student diversity through innovation and educational technology. Practical recommendations include capacity building for teachers through intensive training, utilizing digital technology, and policy support to encourage flexibility in learning. With the right approach, differentiated instruction has the potential to transform Islamic religious education into a more inclusive, applicable, and relevant system for contemporary challenges.